2005
DOI: 10.1128/jvi.79.5.2920-2930.2005
|View full text |Cite
|
Sign up to set email alerts
|

Selective Down-Regulation of the NKG2D Ligand H60 by Mouse Cytomegalovirus m155 Glycoprotein

Abstract: Natural killer (NK) cells are an important defense mechanism against pathogens, particularly against viruses belonging to the herpesvirus family (45, 48). NK cell receptor genes do not undergo somatic recombination and clonal specification (38), and their activation is tightly regulated by a balance of signaling through inhibitory receptors specific for major histocompatibility complex (MHC) class I proteins and activating NK cell receptors with diverse specificities (28). Some activating NK receptors are spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 59 publications
(77 reference statements)
4
76
1
Order By: Relevance
“…Until now, no report including our preliminary study (data not shown) demonstrates that HBsAg has the character. Also, virus proteins such as MCMV m155-, m145-, m152-or m138-encoded glycoprotein may induce the virus infected cells to down-express or upexpress the ligands of activating NK cell receptor (so called ''induced-self'' or ''missing-self'', respectively), by which NK cells may attack self-tissue too [34][35][36][37][38]. We practiced the experiments to explore the ligands of activating NK cell receptor on hepatocytes of HBsAg transgenic mice, and no significant change was found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, no report including our preliminary study (data not shown) demonstrates that HBsAg has the character. Also, virus proteins such as MCMV m155-, m145-, m152-or m138-encoded glycoprotein may induce the virus infected cells to down-express or upexpress the ligands of activating NK cell receptor (so called ''induced-self'' or ''missing-self'', respectively), by which NK cells may attack self-tissue too [34][35][36][37][38]. We practiced the experiments to explore the ligands of activating NK cell receptor on hepatocytes of HBsAg transgenic mice, and no significant change was found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, 11 other ORFs in MCMV were also shown to have MHC-like folds and to be transmembrane glycoproteins (26). Three of these, m145, m152, and m155 have subsequently been shown to sequester stress-induced molecules (MULT1, RAE1, and H60, respectively) that would normally engage the NKG2D-activating NK receptors and interfere with NK cell activation and virus control (27)(28)(29)(30). UL16 of HCMV is known to sequester only some of the human ligands for NKG2D: it does not affect MICA or ULBP3.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations have shown that three other ORFs which had been identified as having MHC-like folds in MCMV, m145 and m155, were able to mediate NK evasion, as these molecules sequestered cellular ligands that would bind the activating NK receptor NKG2D (27)(28)(29)(30).…”
Section: Low Passage and Clinical Isolates Of Hcmv Encode An Additionmentioning
confidence: 99%
“…The mutant virus lacking the m155 gene was also sensitive to NK cell control in vivo, due to its inability to downregulate the NKG2D ligand H60 [50]. We have demonstrated that m155 is able to aVect H60 in isolated conditions, without the involvement of other MCMV proteins.…”
Section: Molecular Mechanisms Of MCMV Regulation Of Nkg2d Ligandsmentioning
confidence: 76%
“…In turn, MCMV regulates the NKG2D ligands MULT-1, RAE-1 and H60 through the m145, m152 and m155 proteins, respectively (Fig. 1b) [48][49][50][51][52]. Furthermore, the deletion of either of MCMV genes encoding inhibitors of NKG2D ligands resulted in rescuing the expression of their target ligand and an enhanced sensitivity of mutant viruses to NK cell control in vivo (Fig.…”
Section: Avoidance Of Nk Cell Activation Via Nkg2dmentioning
confidence: 99%